A systematic review: Are herbal and homeopathic remedies used during pregnancy safe? - Haaritha Boltman-Binkowski (AOSIS, 2016)
Background: Herbal and homeopathic remedies have been used to assist with child bearing and pregnancy for centuries. Allopathic ('Western') medicine is traditionally avoided during pregnancy because of limited drug trials and the suspected teratogenic effects of these medications. This has led to an increase in the use of herbal and homeopathic remedies, asthey are viewed to have no teratogenic effect on the developing foetus. Health providers are faced with questions from their clients regarding the safety of these remedies, but much of the evidence about these herbal and homeopathic remedies is anecdotal and few remedies havebeen tested scientifically. Objectives: By conducting a systematic review, the primary objective was to evaluate maternal and neonatal outcomes of ingested herbal and homeopathic remedies during pregnancy. Method: A systematic review was conducted to synthesise all the evidence with the purpose of evaluating the safety of herbal and homeopathic remedies based on adverse maternal and neonatal outcomes. Only randomised and quasi-randomised controlled trials that met allinclusion criteria were included in the review. Results: The ingestion of ginger for nausea and vomiting during pregnancy was shown to have no harmful maternal or neonatal effects. Ingestion of castor oil for induction of labour showed a tendency towards an increase in the incidence of caesarean section and meconiumstained liquor, warranting further research into its safety issues. Conclusion: Larger randomised controlled trials need to be conducted, especially in South Africa, to establish the safety and efficacy of commonly-used remedies. Keywords: Herbal; homeopathy; birth; pregnancy; labour; intrapartum; nausea; induction of labour